Pembinaan dan Pendampingan Masyarakat dalam Rangka Mewujudkan Pencapaian Ketahanan Pangan Nasional (Food Estate) Provinsi Sulawesi Barat - Jasmin Ambas; Syamsuddin Hasan; Andi Atssam Mappanyukki; Andi Ulfiana Fitri; Meliana Handayani; Syamsu Arif; Amriana Hafiza; Fatmawati Chaerunnisa; Anas Qurniawan (STIKes Ibnu Sina Ajibarang, 2023)
The high number of stunting cases in Indonesia is in the spotlight of WHO, so that stunting cases are given serious attention by the government by making preventing and reducing the number of stunting cases a national program through the collaboration of several ministries. Based on this, the government launched food estates as a national strategic program for 2020-2024. It is hoped that this program will be a solution to overcome the high number of stunting cases while reducing the number of stunting cases that have been found. The food estate program approach, which is expected to have an impact on reducing and preventing stunting cases, uses the